2012
DOI: 10.1007/s10803-012-1650-5
|View full text |Cite
|
Sign up to set email alerts
|

The Specificity of Inhibitory Impairments in Autism and Their Relation to ADHD-Type Symptoms

Abstract: Findings on inhibitory control in autism have been inconsistent. This is perhaps a reflection of the different tasks that have been used. Children with autism (CWA) and typically developing controls, matched for verbal and non-verbal mental age, completed three tasks of inhibition, each representing different inhibitory subcomponents: Go/No-Go (delay inhibition), Dog-Pig Stroop (conflict inhibition), and a Flanker task (resistance to distractor inhibition). Behavioural ratings of inattention and hyperactivity/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 79 publications
2
24
0
Order By: Relevance
“…As studies differed considerably in the inclusion criteria with respect to IQ, we first tested whether IQ was a significant moderator. Please note that not all studies ( n = 7) reported Wechsler scaled IQ [Adams & Jarrold, , ; Ames & Jarrold, ; Jahromi, Bryce, & Swanson, ; Robinson, Goddard, Dritschel, Wisley, & Howlin, ; Sanderson & Allen, ; Yoran‐Hegesh et al., ], therefore these exploratory analyses are based on a subset of the studies included in the planned analyses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As studies differed considerably in the inclusion criteria with respect to IQ, we first tested whether IQ was a significant moderator. Please note that not all studies ( n = 7) reported Wechsler scaled IQ [Adams & Jarrold, , ; Ames & Jarrold, ; Jahromi, Bryce, & Swanson, ; Robinson, Goddard, Dritschel, Wisley, & Howlin, ; Sanderson & Allen, ; Yoran‐Hegesh et al., ], therefore these exploratory analyses are based on a subset of the studies included in the planned analyses.…”
Section: Resultsmentioning
confidence: 99%
“…However, there are also studies that have found no difference between typically developing and ASD individuals in either of these two inhibition domains [prepotent response inhibition: Chan et al., ; Happé & Frith, ; Lee et al., ; Ozonoff et al., ; Schmitz et al., ; Sinzig, Morsch, Bruning, Schmidt, & Lehmkuhl, ; interference control: Goldberg et al., ; Johnston et al., ; Kilinçaslan et al., ; Larson et al., ; Schmitz et al., ; Solomon et al., ; Solomon et al., ; Xiao et al., ]. Given that inhibition is a multifaceted construct, several researchers have tested multiple measures of inhibitory control on a single cohort of participants [Adams & Jarrold, , ; Christ et al., , ; Geurts et al., ; Kilinçaslan et al., ; Sanderson & Allen, ; Xiao et al., ]. Based on multiple measures, Christ and colleagues [Christ et al., , ] concluded that children with autism do encounter interference control deficits (as measured with the Flanker paradigm) but have no problems with inhibiting prepotent responses (as measured with Stroop [like] tasks and the Go/No‐Go task [for contrasting findings, see Geurts et al., ]).…”
Section: Introductionmentioning
confidence: 99%
“…One might also expect a sharper gradient of attention to reduce the interference/enhancement from incongruent/congruent Eriksen flankers in ASC, but the literature is mixed, with some reports of equivalent interference in ASC and controls (e.g. Sanderson and Allen, 2012) and others reporting increased interference (e.g. Adams and Jarrold, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Behavioral performance on flanker tasks is impaired in adults, adolescents and children with ASD relative to comparison groups without ASD (Adams & Jarrold, 2012; Christ et al, 2011; Dichter & Belger, 2008; Geurts, Luman, van Meel, 2008; but see Sanderson & Allen, 2013). Individuals with ASD have slower reaction times and worse accuracy for the incongruent condition relative to comparison groups, and these effects were apparent even when the task was manipulated in ways that make it easier for youth without autism (Adams & Jarrold, 2012).…”
Section: 1 the Flanker Task In Asdmentioning
confidence: 99%